Altered Excitation-Contraction Coupling in Human Chronic Atrial Fibrillation - Grandi, Eleonora (J Atr Fibrillation, 2012)
This review focuses on the (mal)adaptive processes in atrial excitation-contraction coupling occurring in patients with chronic atrial fibrillation. Cellular remodeling includes shortening of the atrial action potential duration and effective refractory period, depressed intracellular Ca(2+) transient, and reduced myocyte contractility. Here we summarize the current knowledge of the ionic bases underlying these changes. Understanding the molecular mechanisms of excitation-contraction-coupling remodeling in the fibrillating human atria is important to identify new potential targets for AF therapy.